Investigating Parental Perspectives on Young Learners’ Social Presence in Online Learning: A Mixed Methods Approach - Song, Jing; Koehler , Adrie; Richardson, Jennifer; Cheng, Zui (Online Learning, 2025)
This study used an explanatory mixed-method approach to understand Chinese parents’ perceived social presence in their children’s online learning and the relationship among parents’ perceived social presence, perceived learning, and satisfaction with their children’s online instructor. In the quantitative phase, 53 Chinese parents of young learners were surveyed to determine the relationship across perceived social presence, perceived learning, and satisfaction with their child’s online instructor. Results highlighted the significant relationships between parents’ perceived social presence and both their perceived learning (r = 0.517) and satisfaction with the instructor (r = 0.518) in their children’s online learning, with social presence accounted for 26.7% of the variance in their perceived learning. Qualitative interviews were conducted to further explore parents’ perceptions of social presence—its definition, importance, the instructor’s roles, parental involvement, and factors impacting perceived social presence. Findings emphasized the importance of parental roles, the interplay of social and teaching presence, and learners’ cultural background when designing effective online learning experiences with young learners.